EVIDENCE-BASED FALLS PREVENTION TRAINING AT A REGIONAL MEDICAL CENTER. (11th November 2018) - Owens, M; Coogle, C; Gentili, A; Marrs, S; Slattum, P; Parsons, P; Waters, L; Ansello, E
Abstract: Falls in older adults should receive interprofessional focus in geriatrics curriculum development because they can be a sentinel event indicating the presence of various risk factors and a triggering event leading to a cascade of deterioration. The American and British Geriatrics Societies' clinical practice guideline and the U.S. Preventative Services Task Force recommendations formed the foundation of a seven week, 24-hour interprofessional training program to promote adoption of falls prevention evidence-based practices (EBPs). Twenty interprofessional trainees who worked in a nursing home or home-based primary care group at a regional medical center participated. We assessed clinician practice change by abstracting electronic medical records (EMRs) information of post-fall patients (N = 99) treated by EBP trainees. Data abstracted at three months prior to training (T1) were compared to the same data points three months post training (T2) and six months post training (T3). Clinicians significantly increased documentation of level of risk (42%, p < .0001), circumstances of fall events (28%, p < .01), causes of falls (32%, p = .02), assessment of risk factors (26%, p =.05), and planned interventions (26%, p=.05). Interprofessional teams articulated plans to improve their assessment procedures and begin implementation of more coordinated care through early, proactive interventions. While nurses tended to be champions for falls assessment and management in the nursing home, the home care providers described a clearer protocol and plan of action to respond to falls. Triangulation of qualitative and quantitative data revealed that pharmacists and occupational therapists were leaders in adopting EBPs.